Prediction of the Likelihood of Households Food Security in the Lake Victoria Region of Kenya - Mwita, Peter N.; Otieno, Romanus Odhiambo; Masanja, Verdiana Grace; Muyanja, Charles (My University, 2011)
This paper considers the modeling and prediction of households food security status using a sample of households in the Lake Victoria region of Kenya. A priori expected food security factors and their measurements are given. A binary logistic regression model derived was fitted to thirteen priori expected factors. Analysis of the marginal effects revealed that effecting the use of the seven significant determinants: farmland size, per capita aggregate production, household size, gender of household head, use of fertilizer, use of pesticide/herbicide and education of household head, increase the likelihood of a household being food secure. Finally, interpretations of predicted conditional probabilities, following improvement of significant determinants, are given
Keywords: Household; Food; Security; Logistic; Probability.